2022
DOI: 10.3389/fenvs.2022.962724
|View full text |Cite
|
Sign up to set email alerts
|

Towards carbon neutrality: Improving resource efficiency of the rare earth elements in China

Abstract: Rare earth elements (REEs) are essential for promoting clean energy technologies and making high-performance materials because of their unique physical and chemical properties. In order to respond to climate change, the Chinese government has promised to achieve carbon neutrality before 2060. Under such a circumstance, the demand for REEs will increase significantly. However, several challenges exist in current REEs supply chain management in China. This policy brief discusses these challenges from a life cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…China's dominance increased, eventually reaching 95% of global production as it acquired stakes in REE firms worldwide, resulting in a "Rare Earth Crisis" in 2010. A dispute between China and Japan led to China imposing restrictions on REE exports, causing prices to surge to 500% in some cases [49]. This incident prompted several nations to reconsider their REE possibilities to reduce their reliance on China.…”
Section: Literature Review and Rare Earth Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…China's dominance increased, eventually reaching 95% of global production as it acquired stakes in REE firms worldwide, resulting in a "Rare Earth Crisis" in 2010. A dispute between China and Japan led to China imposing restrictions on REE exports, causing prices to surge to 500% in some cases [49]. This incident prompted several nations to reconsider their REE possibilities to reduce their reliance on China.…”
Section: Literature Review and Rare Earth Data Sourcesmentioning
confidence: 99%
“…Based on the literature review, it is identified that there is only one study that analyzes the long-term production of rare earths worldwide using quantitative methods [17]. In addition, there are three studies that present the long-term production trajectory of China's rare earths [41,49,77].…”
Section: Limitations and Future Studymentioning
confidence: 99%
“…Given that HREE form more stable complexes with many soil constituents than LREE do [173][174][175], SOM often appears to be enriched in HREE relative to LREE [82,175,176]. Ma et al [177] observed a strong positive Ce-anomaly in REE patterns of organic matter, probably because complexation capacities and formation constants of humic acids are higher with Ce than with the other LREE [178]. In podzols, the percentage of total REE in general, and especially of HREE bound to organic matter, increases with soil depth [82,176] due either to the preferential complexation or the migration of HREE-complexes [82,176].…”
Section: Mobility and Speciation In Soilmentioning
confidence: 99%
“…REE materials are now mostly supplied by China [3], and with demand growing rapidly, there are concerns about supply constraints in the midst of geopolitical tensions [5][6][7][8]. In 2020, the EU started a raw materials alliance focused primarily on REEs and permanent magnet production, as well as a detailed action plan to address possible risks associated with vital raw resources [9]. Notably, for these four elements (Pr, Nd, Dy, and Tb), the intensification in their usage is expected in both low-carbon technologies and other applications.…”
Section: Introductionmentioning
confidence: 99%